Jurnalisme Data dalam Media Online - Dimas Rachmatsyah; Askurifai Baksin (Bandung Conference Series: Journalism, 2023)
Abstract. Data journalism is becoming more up-to-date along with the flood of data on the internet which is often called big data, which triggers the development of tools for collecting and analyzing data. One of the media that provides in-depth news information and uses data journalism in it is Bandungbergerak.id. Media Bandungbergerak.id in their work focuses on data and in-depth reporting, with a focus on issues, one of which is education. This research focuses on data journalism activities on the online media Bandungbergerak.id in terms of making news that uses data on data analysis activities in general in relation to data journalism. Based on that, the writer is interested in researching Data Journalism in Online Media. This study uses a type of qualitative research with a case study approach modeled by Robert K. Yin. The results of the study found that Bandungbergerak.id in its data articles there is a comparison of data with scientific journals. Bandungbergerak.id in the process of making its news prioritizes marginalized issues. Abstrak. Jurnalisme data menjadi lebih mutakhir seiring dengan banjirnya data di internet yang kerap disebut big data, yang memicu perkembangan tools untuk mengumpulkan dan menganalisis data. Salah satu media yang menyajikan informasi berita secara mendalam serta menggunakan jurnalisme data didalamnya yakni Bandungbergerak.id. Media Bandungbergerak.id dalam kerjanya berfokus pada data dan reportase mendalam, dengan fokus terhadap isu salah satunya pendidikan. Penelitian ini berfokus pada aktivitas jurnalisme data pada media online Bandungbergerak.id dari segi pembuatan berita yang menggunakan data pada kegiatan analisis data secara umum dalam kaitannya dengan jurnalisme data. Berlandasan dari itulah penulis tertarik meneliti mengenai Jurnalisme Data Dalam Media Online. Penelitian ini menggunakan jenis penelitian kualitatif dengan pendekatan studi kasus model Robert K. Yin. Hasil penelitian menemukan bahwa Bandungbergerak.id dalam artikel datanya terdapat pembandingan data dengan jurnal ilmiah. Bandungbergerak.id dalam proses pembuatan beritanya mengedepankan isu-isu terpinggirkan.